Family impact on the recovery of critically ill adults: a review of the literature - Ceballos-Vásquez, Paula (Universidad de Sonora, 2021)
Introduction: Critical care units are described by the families of hospitalized individuals as a secluded place, with restricted access, where the severity and complexity of the patient is paramount. Despite evidence of how important it could be to consider and include family members in the recovery of critically ill persons, this has been undervalued and is difficult to achieve due to the complex conditions of these units. Objective: To identify in the literature the impact that the family has on the recovery of hospitalized adults in intensive care units. Methodology: Literature review in the CINAHL Complete, Scopus, PubMed and Scielo databases, by searching for the 2014 to 2019 period of time. Results: 9 articles were analyzed and based on critical reading the most relevant aspects were selected for study. Regarding the distribution by years, 33.3% of the articles were published in 2016. Regarding geographical distribution, 44.4% of the selected manuscripts were written in Europe. Conclusion: There is a research gap that relates the impact of the family on the recovery of the patient. The identified studies show data with positive trends. However, these trends emerge in an indirect way. Therefore, it is proposed to carry out studies that provide innovative strategies with concrete results to verify these benefits, which can be applied in other intensive care units.